Rain of ash Roma, Jews, and the Holocaust - Joskowicz, Ari 1975- (Princeton University Press, 2023)
Introduction: Jews and Roma in the Shadow of Genocide -- 1. Roma and Jews in Nazi Europe -- 2. Surviving Postwar Reconstruction -- 3. Blank Pages: Early Documentation Efforts -- 4. Asymmetrical Justice: Roma and Jews in the Courtroom -- 5. Jewish Institutions and the Rise of Romani Holocaust Scholarship -- 6. The Path to Shared Romani-Jewish Remembrance after 1978 -- Conclusion: Stages of a Relationship